Strategies to Support Children’s Readiness for Elementary School: A Case Study at Sekolah Indonesia Kuala Lumpur - Maera Auliani Riyadi; Suci Utami Putri; Aan Mulyani (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
The transition from Early Childhood Education (ECE) to Elementary School represents a critical developmental phase that requires children’s readiness across independence, social-emotional competence, and cognitive development. In many contexts, school readiness is often narrowly interpreted as academic mastery; however, holistic preparation aligned with developmental stages is essential. This study aims to describe the strategies implemented by Sekolah Indonesia Kuala Lumpur (SIKL) in preparing children at the Early Childhood Education (ECE) level for entry into elementary school. A descriptive qualitative approach was employed, with data collected through interviews involving the school principal, ECE Group B teachers, and first-grade elementary teachers. The findings indicate that although SIKL does not implement a specific transition program, school readiness is systematically integrated into daily ECE learning activities. Strategies include fostering independence, strengthening character development, enhancing social-emotional skills, and adjusting children’s routines through structured yet playful learning experiences. Collaboration with parents and the application of responsive and flexible teaching methods were identified as key supporting factors, while challenges emerged from children’s diverse learning habits and varying levels of independence. The study concludes that effective school readiness preparation should be developmentally appropriate, gradual, and collaborative rather than solely focused on early literacy and numeracy skills. It is recommended that institutions develop structured transition frameworks and strengthen parent–teacher partnerships to ensure smoother adjustment to elementary education.